Risk management in the construction industry in Ukraine - R.S. Makukha (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The effective functioning and recovery of the construction industry in the face of economic instability and war is an essential task for Ukraine. The destruction of infrastructure, reduced demand for construction projects, and logistical difficulties pose complex challenges that require a comprehensive approach. The recovery of the construction industry contributes to the physical restoration of infrastructure and stimulates the countryʼs economic and social development. Attracting financial support from international partners is a crucial element of successful recovery. This article analyzes in detail the role and structure of the construction industry in Ukraine. After the destruction of infrastructure due to the war, the construction industry has become an essential catalyst for physical recovery and economic growth. To provide financial support for recovery efforts, the government has created several specialized funds to help rebuild the countryʼs economy and infrastructure. These investments are expected to contribute to job creation, increased production activity, and economic development. War damage assessments and recovery plans confirm the importance and potential of the construction industry for Ukraineʼs economic recovery. In particular, the plan of the national recovery program for construction and related services in Ukraine includes the modernization of logistics, housing, and infrastructure directing significant financial resources. This is expected to stimulate growth in the construction industry, providing new business opportunities and creating new jobs. However, there are also risks associated with political and physical insecurity, currency depreciation, supply chain disruptions, and labor shortages. To overcome these challenges, a comprehensive approach is needed, including risk management, stabilization of economic conditions, and support for infrastructure projects. In addition, close cooperation between various institutions is needed to effectively address these challenges and ensure the sustainable development of the construction industry in Ukraine.